Impact of COVID-19 epidemic on maxillofacial surgery in Italy. Issue 6 (July 2020) - Allevi, F.; Dionisio, A.; Baciliero, U.; Balercia, P.; Beltramini, G.A.; Bertossi, D.; Bozzetti, A.; Califano, L.; Cascone, P.; Colombo, L.; Copelli, C.; De Ponte, F.S.; et al.
Abstract: Maxillofacial departments in 23 surgical units in Italy have been increasingly involved in facing the COVID-19 emergency. Elective surgeries have been progressively postponed to free up beds and offer human and material resources to those infected. We compiled an inventory of 32 questions to evaluate the impact of the SARS-COV2 epidemic on maxillofacial surgery in 23 selected Italian maxillofacial departments. The questionnaire focused on three different aspects: the variation of the workload, showing both a reduction of the number of team members (-16% among specialists, -11% among residents) due to reallocation or contamination and a consistent reduction of elective activities (the number of outpatient visits cancelled during the first month of the COVID-19 epidemic was about 10 000 all over Italy), while only tumour surgery and trauma surgery has been widely guaranteed; the screening procedures on patients and physicians (22% of maxillofacial units found infected surgeons, which is 4% of all maxillofacial surgeons); and the availability of Personal Protective Equipment, is only considered to be partial in 48% of Maxillofacial departments. This emergency has forced those of us in the Italian health system to change the way we work, but only time will prove if these changes have been effective.